Problematika Kontrak Karya Dalam Hukum Perjanjian Indonesia - Lukman Santoso; Muh Fauzi Arifin (Program Studi Hukum Keluarga Islam, 2019)
This article aims to describe the position of contract work in the legal agreements relating to mining activities in Indonesia. Based on the study of this article, formulated conclusion a few things, first, Indonesia is a country that has abundant natural resources, one of which in mining. In terms of exploration and exploitation of mining, Indonesia still apply cooperation with foreign parties. This provision is stipulated in the law of investment. This cooperation came to be known by the work contract. Second, the work contract is born started when the Indonesian government in April 1967 signed the first contract with Freeport McMoRan mining of the United States. The contract, known as first-generation contract of work. In the contract in principle the right of state control provides the authority to organize, manage and supervise the management or operation of the mine. However, it turns out in praktinya, the management of foreign and precisely controlled by the central government as powerless and not exercise its authority to the fullest.